A Longitudinal Investigation of the Causal Relationship Between Wellbeing and Perceived Discrimination Among Migrant Children in China: The Mediating Role of Self-Esteem and the Moderating Role of School Type - Wang, Qing; Yu, Jie; Tang, Yuanmeng; Luo, Jing; Shi, Baoguo (Frontiers in Psychiatry, 2022)
Background: A large rural labor force has been attracted to urban areas with the acceleration of urbanization in China. This significant change in environment for migrant children from rural to urban may lead to psychological problems, such as decreased subjective well-being (WB) and increased perceived discrimination (PD). However, previous studies have focused on the influence of PD on WB by using a cross-sectional design, ignoring the causality and intrinsic mechanisms between WB and PD. The current study investigates the causal association and internal relations between migrant children’s PD and WB. Methods: A total of 466 (222 females, 47.64%) migrant children (Mage = 11.78, SD = 1.80) were recruited from Beijing in China. The participants filled in the questionnaire twice, with an interval of one year, including a basic information questionnaire, well-being index scale, perceived discrimination questionnaire, and self-esteem scale. Results: Overall, cross-lagged regression analysis revealed that WB (T1) had a predictive effect on PD (T2) but that PD (T1) had no predictive effect on WB (T2). Mediation results indicated that self-esteem (SE) (T1) mediated the relation between WB (T1) and PD (T2). Moderated mediation results further proved that the link between WB (T1) on SE (T1) and the indirect effect between WB (T1) and PD (T2) were more robust for migrant children who attended public school than those in the migrant children’s school. Conclusion: These findings implied that a decrease in WB may increase the perception of subjective discrimination and that SE could be an intrinsic factor between migrant children’s WB and PD, especially in public schools. Therefore, educators and parents should also pay attention to mental health problems to improve the well-being and self-esteem of migrant children.